PENAFSIRAN AYAT-AYAT LARANGAN MEMILIH PEMIMPIN NON-MUSLIM MENURUT SAYYID QUTHB - Erita Erita (UIN Imam Bonjol Padang, 2018)
Non-Muslim leadership becomes a problematic issue in the context of inter-religious relations nowadays, especially for Muslims in conducting religious-social-political relations with non- Muslims. Historically, the issue has been going on for a long time and always invites debates among the Muslim scholars from time to time. In response to this issue, the scholars are divided into two camps, most of them forbid it but others allow. One of the scholars forbidding the choosing of Non-Muslim leadership was Sayyid Quthb, as can plainly be seenon his statement,